2017
DOI: 10.1109/tpel.2016.2641260
|View full text |Cite
|
Sign up to set email alerts
|

Class-E Half-Wave Zero dv/dt Rectifiers for Inductive Power Transfer

Abstract: This paper analyses and compares candidate zero dv/dt half-wave Class-E rectifier topologies for integration into multi-MHz inductive power transfer (IPT) systems. Furthermore, a hybrid Class-E topology comprising advantageous properties from all existing Class-E half-wave zero dv/dt rectifiers is analysed for the first time. From the analysis, it is shown that the hybrid Class-E rectifier provides an extra degree of design freedom which enables optimal IPT operation over a wider range of operating conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The inherent regulation properties of resonant converters can sometimes be used to maintain soft switching, for instance, non-synchronous Class E rectifiers inherently change the duty cycle of the diode when the dc-load changes, and consequently achieve ZVS. Furthermore, in [21] a hybrid Class E rectifier (a Class E rectifier with an additional capacitance that provides an additional degree of design freedom) not only achieves ZVS, but also can be designed to inherently regulate the output voltage as the load changes. The inherent regulation properties of resonant converters have been utilised for multiple purposes, for example in [22] the resonant nature of a LCC converter was utilised for power factor correction, and in [23] an inherent over-current protection feature was implemented by placing an auxiliary circuit in parallel with the resonant capacitor of a LLC resonant converter which shorts the capacitor and detunes the resonant tank when a fault shorts out the load.…”
Section: Inherent Regulation In Resonant Converters For Variablementioning
confidence: 99%
“…The inherent regulation properties of resonant converters can sometimes be used to maintain soft switching, for instance, non-synchronous Class E rectifiers inherently change the duty cycle of the diode when the dc-load changes, and consequently achieve ZVS. Furthermore, in [21] a hybrid Class E rectifier (a Class E rectifier with an additional capacitance that provides an additional degree of design freedom) not only achieves ZVS, but also can be designed to inherently regulate the output voltage as the load changes. The inherent regulation properties of resonant converters have been utilised for multiple purposes, for example in [22] the resonant nature of a LCC converter was utilised for power factor correction, and in [23] an inherent over-current protection feature was implemented by placing an auxiliary circuit in parallel with the resonant capacitor of a LLC resonant converter which shorts the capacitor and detunes the resonant tank when a fault shorts out the load.…”
Section: Inherent Regulation In Resonant Converters For Variablementioning
confidence: 99%
“…Resonant rectifiers have important roles in many applications such as wireless power transfer (WPT) systems [1][2][3][4][5][6][7], rectifier part of the resonant DC-DC converters [8][9][10][11][12][13][14][15][16], and energy harvesting circuits [17]. The resonant rectifiers are suitable for high-frequency and high-efficiency operations due to the soft switching [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]17]. For designs of the resonant rectifier, it is important and helpful to comprehend typical characteristics, for example, AC-to-DC transfer function, peak voltage across the rectifier diode, and power output capability.…”
Section: Introductionmentioning
confidence: 99%
“…The receiving coil was formed by copper plating the propeller guard of the drone forming a single-turn 330-nH coil. The rectifier on-board the drone was a hybrid Class E rectifier introduced in [26]. Thermal imaging showed that when the drone was at its furthest point away from the transmitting coil, the diodes were contributing to the majority of the losses in the rectifier, since the rectifier operates at a low-voltage high-current regime.…”
Section: -W 1356-mhz Synchronous Class E Rectifier In Wireless mentioning
confidence: 99%